BS EN IEC 61076-8-103. Connectors for electrical and electronic equipment. Product requirements. Part 8–103. Power connectors. Detail specification for 2P+PE circular connectors with 20 A rated current and push-pull locking IP65/IP67 metal housing (16th July 2021) - British Standards Institution,
No abstract available